Representations of the ruling icon in modern European painting - Omar Ali Mustafa; Alaa Ali Ahmad (Basrah Arts Journal, 2023)
The research dealt with the topic representations of the ruling icon in modern European painting which concerned the issue of ruling icons through their employment and uses in European painting, and included four chapters: the first of which concerned the methodological framework of the research, and contained the research problem in which light was highlighted on (the ruling icons in Modern European painting), and the research problem was identified by answering the following question: What are the ruling icons in modern European painting? As for the second chapter, it included the theoretical framework, which contained two sections, the first included the concept of the ruling icon, while the second chapter included the ruling icon in modern European painting, while the third chapter was concerned with the research procedures, and the fourth chapter contained results and conclusions, including: The icon in European painting relied on the emotional impact of colors and shapes, and the artist used a way to communicate their inner feelings such as fear and sadness, and their works became . Contemporary painters added the religious figure in their works, and this employment came to bear key characteristics . The icon took its place in the contemporary arts, which were able to develop forms that carry iconographic connotations with religious dimensions, in principle, to serve the secrets of the faith or to simplify its concepts and consolidate them in the minds of the societies that we see to this day as a system immortalized by legends.